Effects of coloring procedures on shear bond strength between resin cement and colored zirconia - İlkin Tuncel; Işıl Turp (Istanbul University, 2018)
Purpose Debonding is expected as a frequent failure type in zirconia restorations. Therefore the aim of the current study is to evaluate the shear bond strength between colored zirconia and resin cement. Materials and methods There were 11 groups evaluated each containing 12 zirconia discs (15 mm x 12 mm x 1.6 mm). Groups were colored with the colors A3, B1, C4, D2, and D4 of the VITA classical shade scale. Coloring procedure was carried out for either 3 second or 60 seconds for the study groups and the control group was left untreated. Specimens were then bonded to translucent resin cement having a thickness of 3 mm and width of 3 mm. The shear bond strength of the samples was measured in a universal testing machine with a crosshead speed of 1 mm per minute. Two-way analysis of variance and Tukey's HSD test were used for pairwise comparisons. Also paired t-test was used for comparing groups with the same color but having different shading times. Results Any significant difference was not found between the shear bond strengths of samples depending on whether color or shading times. Among the groups, B1 (60 seconds of coloring) had the highest bond strength (10.05 MPa), while A3 (60 seconds of coloring) showed the lowest bond strength (6.72 MPa). However, these differences were not statistically significant. Conclusion Coloring zirconia did not affect the shear bond strength between zirconia and resin cement.